The Effect of Capital Structure and Dividend Policy on Company Value with Family Ownership as A Moderating Variable - Nadiya Yunan; Rudy Syafariansyah Dachlan; Shinta Natali (Journal of Creative Power and Ambition (JCPA), 2026)
The primary objective of every company is to maximize firm value because higher firm value reflects better company performance and increases shareholder wealth. The purpose of this study was to determine the effect of capital structure and dividend policy on firm value, as well as the role of family ownership in moderating these two relationships in Salim Group companies for the 2019–2023 period. The research method used was a quantitative approach with panel data regression analysis techniques and SPSS version 25 statistical analysis tools to determine the influence and relationship of each variable. The analysis revealed that capital structure had no significant effect on firm value (p-value 0.196 > 0.05), while dividend policy had a significant positive effect on firm value (p-value 0.005 < 0.05). Furthermore, family ownership did not moderate the effect of capital structure on firm value (p-value 0.409 > 0.05) or the effect of dividend policy on firm value (p-value 0.466 > 0.05).